PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS VII SMPN 1 INUMAN - Kasman Bamba (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
he background of this study is the low learning outcomes of English students. Of the 22 students only 9 studentsreached KKM. On this basis researchers do research by applying cooperative learning model type NHT toimprove English learning outcomes. This research is a classroom action research conducted in SMPN 1 Inuman,the subject of this study is the students of class VII with the number of 22 students. The results suggest that thelearning outcomes of English have increased in each cycle. This is evidenced by: In the basic score of thenumber of students who reached KKM or complete is 9 students (40.90%), the UH I has increased with thenumber of 17 students (77.27%) and in UH II increased with the number of 20 students (90.90%). In the basicscore of the learning result of the students get the value of 51,25 with the low category, at UH I experiencing theincrease of learning result with the acquisition value of 65,76 with the medium category, and at UH II studentlearning result again increase with the acquisition value equal to 79,25 with high category.